What determines fiscal balances? An empirical investigation in determinants of changes in OECD budget balances - Mika Tujula; Guido Wolswijk (European Central Bank (ECB), 2004)
Fiscal balances have deteriorated quickly in recent years, bringing back to the foreground the question what factors help explain such sharp changes. This paper takes a broad perspective at the issue regarding countries included, the range of explanatory variables tried, and the time-span. The empirical analysis shows that changes in budget balances are affected by debt growth, macroeconomic developments and political factors. In particular, we find that the run-up to EMU induced additional consolidation in Europe and that budget balances deteriorate markedly in election years. Asset prices also may affect budgets, but the impact remains limited in normal times.
Keywords: E61; E62; H61; H62; 330; asset prices; budget balance; Economic Growth; Fiscal Policy; Stability and Growth Pact